Woman suffrage and women's rights - DuBois, Ellen Carol, 1947- (New York University Press, 1998)
This volume gathers DuBois' most influential articles on woman suffrage and includes two new essays. The collection traces the trajectory of the suffrage story against the backdrop of changing attitudes to politics, citizenship and gender, and the resultant tensions over such issues as slavery and abolitionism, sexuality and religion, and class and politics. Connecting the essays is DuBois' belief in the continuing importance of political and reform movements as an object of historical inquiry and a force in shaping gender.